Impact of Computer Integrated Technique in Science Education at Elementary Level: A Study in Karachi - Salman Ashiq; Habib, Zehra (Journal of Education and Educational Development, 2020)
Computer technology plays an active role in the development of the economic, educational, and social growth of a country. Following a sequential explanatory mixed methods research design, the primary purpose of the study was to comprehend the advantages of teaching science to grade 6 students via Computer Integrated Teaching (CIT) as compared to the lecture-based approach. This study also investigated if computer integrated teaching enhanced students learning and contributed to higher achievement scores. The research was conducted for 6 months, with a focus on grade 6 science instruction. The quantitative part of the study comprised experimental research with a sample size of 62 students. Experimental group students were exposed to a strong intervention program of CIT, whereas the control group was taught by traditional methods. The findings of the study show that the experimental group scored significantly higher marks in science theory and practical tests than the control group students. The qualitative findings of the study, based on focus group interviews, support the quantitative findings as students favored technology-based learning because of its vast potential.
Keywords: computer integrated teaching (CIT); elementary level; information and communication technology (ICT)